(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Kadamb an indigenous plant described in classical texts of Ayurved has a wide range of therapeutic potential. In Charak Samhita, it has been classified in the group of drugs indicated in the management of pain (Vednasthapan Mahakashya). Among various indications, it has been reported to be used in the treatment of vitiated semen, as an astringent in healing of fractured wounds, hemorrhagic conditions, dyslipidaemia, diseases of female genital tract, as complexion promoting and alexipharmic. In classical texts, at least four varieties of Kadamb have been described. There has always been some controversy regarding botanical identity of different varieties of Kadamb described in classical texts. Present paper is a serious attempt towards establishment of botanical identities of different types of Kadamb described in classical text of Ayurved on the basis of exploration of literature substantiated by observations of field survey.